The Use of Gamification for Pre-Recruitment System in Tax Consulting Company - Muthia Maharani; Gunawan Wang (Journal of Information System and Informatics, 2022)
The increasing need for employees who are experts in the IT field, or commonly referred to as digital talent, is a new challenge for the human resources department in the era of digital transformation. The results of interviews and observations conducted at a tax consulting company show that the HR department does not have a definite procedure for measuring the technical capabilities of IT candidates. Because technology is always changing and evolving, it is difficult to locate someone who is already conversant with the most current technologies and techniques. Assessing a candidate's genuine potential is more difficult than merely reading it on a CV or asking, "can you accomplish this?" or "do you have this trait?" Previous research indicates that the majority of candidates lie about themselves on their resumes and hiring managers just don't care. Having a qualified digital talent is critical while the tax company undergoes digital transformation. With Gen Z and millennials as recruitment targets, this study proposes a solution by designing a gamification using the MDE framework. Gamification has been shown to be effective in attracting and assessing fresh talent throughout the recruiting process. The purpose of this study is to investigate how gamification might attract skilled IT applicants while avoiding errors in judging their genuine potential.